Clinical significance of C-reactive protein/platelet ratio from diagnosis to allogeneic hematopoietic stem cell transplantation in acute myeloid leukemia - Izumi, Akihiko; Tachibana, Takayoshi; Nukui, Jun; Miyazaki, Takuya; Hirose, Natsuki; Ohashi, Takuma; Tanaka, Marika; Katsuki, Kengo; Suzuki, Taisei; Nakajima, Yuki; Matsumoto, Kenji; Fujisawa, Shin; et al. (Annals of hematology, 2025)
Previous studies have shown that C-reactive protein/platelet ratio (CPR) before allogeneic hematopoietic stem cell transplantation (HSCT) is a predictor of survival in patients with hematological malignancies. This multicenter retrospective study aimed to evaluate the clinical significance of CPR from diagnosis to HSCT in patients with acute myeloid leukemia (AML) who underwent HSCT. This cohort included patients with AML who underwent their first HSCT between 2016 and 2021. CPR was evaluated at three time points: at diagnosis, after initial therapy, and pre-HSCT. The cut-off value for CPR was set at 0.05 based on previous studies. In total, 196 patients with a median age of 50 years (range: 15–72). High CPR was associated with the myeloblast ratio in the bone marrow at three points and was associated with high transfusion volume and poor performance status at HSCT. Overall survival (OS) at 2 years according to CPR at diagnosis, after initial therapy, and pre-HSCT (low vs. high) was 67.9% vs. 65.6% ( P = 0.477), 72.6% vs. 54.8% ( P = 0.022), and 73.1% vs. 49.7% ( P < 0.001), and non-relapse mortality (NRM) was 15.8% vs. 19.0% ( P = 0.557), 13.8% vs. 21.5% ( P = 0.201), and 13.0% vs. 27.6% ( P = 0.006), respectively. No significant differences were observed in the relapse rates. In multivariate analysis, the high CPR group pre-HSCT was associated with poor OS (HR = 1.86, 95%CI:1.13–3.07, P = 0.015) and higher NRM (HR = 2.52, 95%CI:1.26–5.04, P = 0.009). Pre-HSCT CPR was associated with post-HSCT OS and NRM. CPR is considered a marker that reflects the disease status and patient condition, suggesting the significance of CPR monitoring.